STUDY OF THE EFFECT OF NEW SYNTHESED COMPLEX CHEMICAL ADDITIONS ON RHEOLOGICAL PROPERTIES OF PORTLAND CEMENT (Innovative Technologica: Methodical Research Journal, 2021)
This article examines the effect of newly synthesized complex chemical additives KDj-3 and KDj-3MB on the kinetics and water requirements of Portland cement on the basis of local raw materials. The use of complex additives in the production of concrete mixes significantly reduces the negative impact of each additive. In this way, the universality of additives can be achieved in the production of concrete mixes and compositions made of cements of different brands. Because complex admixtures are so convenient, it is not necessary to use several components to obtain concrete with the desired properties.